Changes of physicochemical indexes and flavor substances of fermented grains at different spatial levels during Northern strong-flavor Baijiu fermentation - WANG Le, WEI Gong, GUO Yizhen, LIU De, WANG Hui, ZHANG Min, SHI Hui, QU Hui, HE Yunjun, REN Guojun, YAN Wei (Zhongguo niangzao)
The changes of physicochemical indexes and main flavor substances in six position points of fermented grains at different spatial levels during the fermentation of Northern strong-flavor (Nongxiangxing) Baijiu were studied. The results showed that the changes of physicochemical indexes and flavor substances in fermented grains at different spatial levels showed certain regularities. The changes in contents of moisture, acidity, starch, butyric acid, caproic acid, isoamyl alcohol and n-butanol in fermented grains were consistent at the four position points of middle and upper layer, but different from those at the two position points of bottom layer. The changes in the contents of residual sugar, ethyl lactate, acetaldehyde, acetic acid, propionic acid and methanol in fermented grains were basically the same at six position points, but the changes in the contents of acetal, isobutanol, n-propanol and secondary butanol were different at each position points. The change trajectories of ethyl caproate and ethyl butyrate were not detected at three position points, while the other three position points were different. The contents of caproic acid and n-butanol in the bottom layer were significantly higher than those in the middle and upper layer, the increase of ethyl lactate in the middle and upper layer was much greater than that in the bottom layer, and the content of 2-butanol in the middle and bottom layer was significantly increased, but there was no significant change in the upper layer. The content of residual sugar in the center points of middle and bottom layer was significantly higher than that at the pit side points, and there was no significant difference in starch content between the center points and the pit side points. The content of methanol, caproic acid, n-propanol and isoamyl alcohol in the pit side points was significantly higher than that at the center point of at the same layer, while the contents of isobutanol were the opposite. Ethyl caproate and ethyl butyrate were mainly produced by the fermented grains at pit side points of bottom and middle layer during the middle and late stages of fermentation.